Estimation of the Madeira floodplain dynamics from 2008 to 2018 - Guilhen, Jérémy; Parrens, Marie; Sauvage, Sabine; Santini, William; Mercier, Franck; Al Bitar, Ahmad; Fabre, Clément; Martinez, Jean-Michel; Sànchez-Pérez, José-Miguel (Frontiers in Water, 2022)
The Madeira is one of the major tributaries of the Amazon River characterised by a large alluvial floodplain throughout the stream continuum. This study aims to better assess the hydrological functioning of the Madeira Basin over its alluvial floodplains at both local and global scales. We used the semi-distributed hydrological Soil and Water Assessment Tool (SWAT) model to simulate water discharge at a daily time step and water resources for each hydrological compartment. A new hydraulic module for water routing was implemented in the SWAT model considering the floodplain either as a simple reservoir or as a continuum where the water can flow along with the floodplain network. Both water surface estimated by L-band passive microwaves (SWAF data) and Digital Elevation Model (DEM - SRTM data) were used for the floodplain delineation as inputs for the model. At the global scale, the amount of water stored in the Madeira floodplain is between 810 ± 230 km3 per year when the floodplains is delimited with SWAF and 1,300 ± 350 km3 per year with the DEM floodplain delineation between 2008 and 2018. Spatial altimetry (Jason 2-3) data were also applied to alluvial areas to validate the water height dynamic in floodplains at local scale. Results show that more than 60% of the alluvial validation points display a correlation above 0.40 ± 0.02 regardless the floodplain delineation. This study permits to better characterize the spatio-temporal storage dynamics of the Madeira floodplains at both local and global scale and it underlines the importance of a precise floodplain delineation, before computing biogeochimical fluxes and sediment yield.